2016
DOI: 10.1038/boneres.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

The biological function of type I receptors of bone morphogenetic protein in bone

Abstract: Bone morphogenetic proteins (BMPs) have multiple roles in skeletal development, homeostasis and regeneration. BMPs signal via type I and type II serine/threonine kinase receptors (BMPRI and BMPRII). In recent decades, genetic studies in humans and mice have demonstrated that perturbations in BMP signaling via BMPRI resulted in various diseases in bone, cartilage, and muscles. In this review, we focus on all three types of BMPRI, which consist of activin-like kinase 2 (ALK2, also called type IA activin receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 98 publications
2
42
0
1
Order By: Relevance
“…The analysis of potential changes in gene expression of BMP type I and type II receptors showed that PEMFs or BMP2 used alone or in combination could increase ALK2 expression in the middle late phase of cell differentiation. This result appears of interest because of the key role of ALK2 in the osteogenic differentiation induced by several osteogenic BMPs and suggests that PEMFs and BMP2 may act through a modulation in BMP2 or BMP6 utilization as these BMPs predominantly act by this type I receptor in hMSCs [32,33]. Further, our observation is in agreement with previous studies showing that ALK2 expression may be upregulated through BMP/SMAD signaling in MSCs [34].…”
Section: Discussionsupporting
confidence: 92%
“…The analysis of potential changes in gene expression of BMP type I and type II receptors showed that PEMFs or BMP2 used alone or in combination could increase ALK2 expression in the middle late phase of cell differentiation. This result appears of interest because of the key role of ALK2 in the osteogenic differentiation induced by several osteogenic BMPs and suggests that PEMFs and BMP2 may act through a modulation in BMP2 or BMP6 utilization as these BMPs predominantly act by this type I receptor in hMSCs [32,33]. Further, our observation is in agreement with previous studies showing that ALK2 expression may be upregulated through BMP/SMAD signaling in MSCs [34].…”
Section: Discussionsupporting
confidence: 92%
“…After bioinformatics analysis, we ltered that ACVR1, also known as ALK2, a member of bone morphogenetic protein receptors type I, was another target of bta-miR-365-3p. As an essential member of TGF-Ī² family, ACVR1 has been reported to play functional roles in early embryonic development [48], lens formation [49], chondrogenesis, osteogenesis [50,51] and cardiac hypertrophy [52]. Additionally, recurrent heterozygous mutations of ACVR1 have been associated with diseases in human such as bro dysplasia ossi cans progress (FOP) [53], diffuse intrinsic pontine gliomas (DIPGs) [54] and pediatric midline high-grade astrocytoma (mHGAs) [55].…”
Section: Gene Targets Of Mir-365-3pmentioning
confidence: 99%
“…After bioinformatics analysis, we identi ed that ACVR1, also known as ALK2, a member of bone morphogenetic protein receptors type I, was another target of bta-miR-365-3p. As an essential member of TGF-Ī² family, ACVR1 has the functional roles in early embryonic development [48], lens formation [49], chondrogenesis, osteogenesis [50,51] and cardiac hypertrophy [52]. Additionally, recurrent heterozygous mutations of ACVR1 were associated with diseases in human such as bro dysplasia ossi cans progress (FOP) [53], diffuse intrinsic pontine gliomas (DIPGs) [54] and pediatric midline high-grade astrocytoma (mHGAs) [55].…”
Section: Gene Targets Of Mir-365-3pmentioning
confidence: 99%